THE EFFECT OF TAX RATE, TAX AWARENESS AND PENALITIES ON TAX PAYER COMPLIANCE AT SMEs IN REJOTANGAN TULUNGAGUNG - Novita Eksanti Rahayu; Citra Mulya Sari (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2022)
Abstract The purpose of this research is to examine the effect of tax rates on taxpayer compliance of SMEs in Rejotangan Tulungagung district. To test the effect of sensitization on taxpayer compliance with SMEs in Rejotangani Tulungagung District, to examine the effect of tax penalties on SMEs taxpayer compliance in Rejotangani Tulungagung District. To examine the effect of tax rates, tax awareness and penalties on taxpayer compliance by SMEs in Rejotangan Tulungagung District. The research approach used is a quantitative approach, of the associative research type. The population used in this study consisted of all SMEs in Rejotangan district, with a total of 85 SMEs selected using the random sampling technique. Data analysis used the multiple linear regression method. The results of this study, namely: (1) There is a significant effect of tax rates on taxpayer compliance of SMEs actors in Rejotangan Tulungagung district. The amount of the tax rate which is the stipulation also makes the reason why the taxpayer pays the tax. (2) There is a significant effect of sensitization on tax compliance of SMEs in Rejotangan Tulungagung district. Taxpayers make tax payments due to self-awareness or encouragement from other parties. (3) Tax penalties have a significant effect on taxpayer compliance of SMEs actors in Rejotangan Tulungagung district. The application of tax penalties that create a deterrent effect, so that subsequent payments are better directed. (4) There is a significant effect of tax rates, awareness and tax penalties on taxpayer compliance of SMEs actors in Rejotangan Tulungagung district. Therefore, it is important for the parties involved to consider various factors that influence taxpayer compliance. Keywords: SMEs, tax rate, tax awareness, penalties for taxpayer compliance